ANALISIS PENGENDALIAN PERSEDIAAN PRODUK DENGAN METODE EOQ BERBASIS WEB - Rekhi Thiara; Ardi Wijaya; Pahriza Pahriza; Khairullah Khairullah (UNIVED Press, 2024)
Inventory management is a crucial aspect in maintaining business operations. This article discusses the implementation of the Economic Order Quantity (EOQ) method in inventory control of products using a web-based application. The EOQ method is employed to optimize the most efficient order quantity while considering ordering costs and holding costs. In this study, we emphasize the significance of proper inventory management in ensuring product availability. Distributors or companies require an accurate calculation system to determine the appropriate order quantity and timing. Errors in inventory management may lead to missed sales opportunities or detrimental excess inventory. The utilization of computer technology is pivotal in expediting and enhancing decision-making processes related to inventory. The EOQ method is systematically implemented through a web-based application to facilitate intelligent product inventory planning. This application enables the calculation of crucial parameters such as Economic Order Quantity (EOQ), Reorder Point, and Total Costs. The findings of this research demonstrate that the implementation of the EOQ method in inventory management has positive effects in addressing stockouts and excess inventory issues. Furthermore, companies can reduce overall inventory costs by optimizing resource utilization. The web-based application with the EOQ method provides an effective solution for achieving efficiency and cost reduction in product inventory operations